KONSEP AL-QAWAMAH DALAM TAFSIR AL-MANAR KARYA MUHAMMAD ABDUH: KONSEP AL-QAWAMAH DALAM TAFSIR AL-MANAR KARYA MUHAMMAD ABDUH - Maulida, Fahma; Khayyinatun Herlina (JIPSKi: Jurnal Ilmu Pendidikan dan Studi Keislaman, 2024)
This research is motivated by the debate on the meaning of al-qawa>mah among the mufassirs, which makes it an excuse for the absoluteness of male leadership over women. This view has legitimised the role of women as leaders. In this case, Muhammad Abduh believes that leadership is not absolute for men because fadhl (the ability to earn a living) can also be done by women. Therefore, the focus of this study is on Muhammad Abduh's concept of al-qawa>mah in QS. an-Nisa'[4]: 34. The method used by the author is a descriptive-analytical method with a historical-sociological approach. Based on the results of the analysis, it is concluded that Muhammad Abduh's interpretation of the memorisation of al-qawa>mah is not absolute for men, because the form of male leadership over women in question is democratic leadership, namely leadership that gives the led the freedom to act according to their will and not leadership that is coercive. Keywords: Al-Qawa>mah, Women Leadership, Tafsir Al-Mana>r